Exploration Of Halal Standard Implementation In The Hospitality Industry In Indonesia - Maulana, Nora; Siregar, Ihsan Mulia (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
The outbreak of the Islamic economic trend has become a branding that currently attracts the attention of many business people from various sectors including the hotel industry. Moreover, Indonesia as the world's largest Muslim country, of course, this condition is a momentum for business people to develop their businesses. Karena islamic branding is not just a form of Muslim compliance with sharia, but also an attraction and lifestyle of the community. This perception has become the trigger for the rise of businesses using sharia identity which cannot be ascertained the correctness of the labeled sharia discrimination. This study aims to see the suitability of sharia hotel implementation with the regulators compiled by DSN-MUI. This research is a fieldresearch with an exploratory descriptive qualitative approach, data collection techniques obtained through observation, depth interviews, and documentation. Data analysis was carried out using the Spradley method in stages ranging from domain analysis, taxonomy, componential and finally analysis of cultural topics. The results showed that the implementation of sharia principles has not been fully applied properly to Namira Hotel Syariah Yogyakarta, especially the aspect of recruiting employees who still prioritize Muslims, worship management has not been managed evenly, hotel operations do not have sharia supervisors and moreover Namira Hotel Syariah does not yet have an official permit for DSN-MUI halal certification, p Sharia endalilan is based on the wishes of business people, not from sharia selection and standardization.  The results of the research findings can be used as material for evaluation and quality assessment standards for the implementation of sharia hotels in Indonesia based on DSN-MUI fatwa No. 108 of 2016.